(3cJGH aj ThGP GdbQGAI hGNJdGa GdeUGMas - (3eMeO Hf CHj fUQ Hf YHO Gddg GdcQeGfj, QVj GdOjf CHh YHO Gddgs
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdYGde QVj GdOjfgPG cJGH LeYJg aj HjGf ThGP GdbQGAI hGNJdGa GdeUGMa s
(3BNQgG (B:s
(3cPdc Yf jYbhH QMeg Gddg hYf GdMSf Ydi GdfaKGJ HZjQ Cda hYf MejO hGdMSf s
(3GdfSNI HgG MhGTs
(3HBNQg hbaI cJH ef CKfGA ShQI Gdadbs
(3JHUQI GdYfhGf (B:s
(3LeY s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdbQGAGJ hGdJLhjOs